2020
DOI: 10.1017/jfm.2020.903
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent channel flow of generalized Newtonian fluids at a low Reynolds number

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
5
13
0
Order By: Relevance
“…Many experimental (Park et al 1989;Pinho & Whitelaw 1990;Pereira 1994) and numerical (Rudman & Blackburn 2003Gavrilov & Rudyak 2016) studies have reported features common to the low drag reduction (LDR) regime (Warholic, Massah & Hanratty 1999), such as enhancement of streamwise turbulence intensity and suppression of other cross-sectional intensities, decrease in Reynolds shear stress and overall reduction of turbulent production with shear-thinning fluid behaviour. More recently, and based on observations of the Reynolds stress budgets and to the overall turbulent kinetic energy, for turbulent pipe (Singh, Rudman & Blackburn 2017) and channel (Arosemena et al 2021) flows, strain-rate-dependent rheology has been found to be mainly important within the inner layer region. This remark is supported as well by the Singh, Rudman & Blackburn (2016) results where, for a fixed GN fluid rheology within the inner layer region, no significant differences are observed in the mean-flow and first-order statistics even if different apparent fluid viscosity profiles are attained outside the inner layer.…”
Section: Rheological Drag Reduction In Generalized Newtonian Fluidsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many experimental (Park et al 1989;Pinho & Whitelaw 1990;Pereira 1994) and numerical (Rudman & Blackburn 2003Gavrilov & Rudyak 2016) studies have reported features common to the low drag reduction (LDR) regime (Warholic, Massah & Hanratty 1999), such as enhancement of streamwise turbulence intensity and suppression of other cross-sectional intensities, decrease in Reynolds shear stress and overall reduction of turbulent production with shear-thinning fluid behaviour. More recently, and based on observations of the Reynolds stress budgets and to the overall turbulent kinetic energy, for turbulent pipe (Singh, Rudman & Blackburn 2017) and channel (Arosemena et al 2021) flows, strain-rate-dependent rheology has been found to be mainly important within the inner layer region. This remark is supported as well by the Singh, Rudman & Blackburn (2016) results where, for a fixed GN fluid rheology within the inner layer region, no significant differences are observed in the mean-flow and first-order statistics even if different apparent fluid viscosity profiles are attained outside the inner layer.…”
Section: Rheological Drag Reduction In Generalized Newtonian Fluidsmentioning
confidence: 99%
“…Singh, Rudman & Blackburn (2018) also reported small contributions from viscosity fluctuation terms to the mean shear stress budget, mean flow and turbulent kinetic energy budget up to moderate frictional Reynolds numbers, Re τ = 323-750. Arosemena et al (2021) further reasoned that observed drag-reducing features with shear-thinning behaviour are likely related to important changes to the near-wall turbulent structures and, in consequence, to the self-sustaining process occurring near the wall.…”
Section: Rheological Drag Reduction In Generalized Newtonian Fluidsmentioning
confidence: 99%
See 3 more Smart Citations